Эммануэль: роман : [перевод с французского] / Эммануэль Арсан - Арсан Эммануэль (СТД Грузии, 1991)
Экземпляры: ф.2 (1993) / Инвентарный номер: 36573 / Сис.шифр: 84(4Фра)-4 / Авт.знак: А 85 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-44